2011
DOI: 10.1007/s10853-011-6139-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of LiFePO4/C composite as a cathode material for lithium-ion battery by a novel two-step method

Abstract: In this study, LiFePO 4 /C is synthesized via a novel two-step method. The first step is the synthesis of nano-sized intermediate FePO 4 by a modified sol-gel method. A fast and full combustion procedure is involved to remove carbon and control the size of the intermediate particles. The second step is to prepare LiFePO 4 /C by combining solid-state reaction with controllable carbon coating. This two-step method is facile to prepare nanosized LiFePO 4 and easy to optimize the carbon content for surface coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, it can also be found that the capacities are not stable for the initial few cycles. This unstable capacity may be attributed to the contact time between the electrode materials and electrolyte too short, resulting in an insufficient "activation" [32].…”
Section: Electrochemical Performance In Non-aqueous Lithium Ion Batterymentioning
confidence: 99%
“…However, it can also be found that the capacities are not stable for the initial few cycles. This unstable capacity may be attributed to the contact time between the electrode materials and electrolyte too short, resulting in an insufficient "activation" [32].…”
Section: Electrochemical Performance In Non-aqueous Lithium Ion Batterymentioning
confidence: 99%
“…Recently, the lithium transition metal phosphates such as LiMPO 4 (M = Co, Mn, Fe, Ni) [5][6][7] and Li 3 M 2 (PO 4 ) 3 (M = V, Fe) [8,9] have been proposed as the next generation cathode materials for LIB because of their appealing features of good thermal stability and high operation potential [10,11]. Olivine-type LiFePO 4 (LFP) and monoclinic Li 3 V 2 (PO 4 ) 3 (LVP) are the two typical representatives.…”
Section: Introductionmentioning
confidence: 99%
“…2e). It is well known that the surface of LiFePO4 coated with a carbon layer can effectively inhibit the particle growth and enhance the electrochemical properties [23]. The lattice fringes with a width of 0.39 nm correspond to the (210) plane of LiFePO4 (Fig.…”
Section: Resultsmentioning
confidence: 99%